2008
DOI: 10.1093/jn/138.3.599
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Feeding Patterns, Time to Initiation, and Mortality Risk among Newborns in Southern Nepal

Abstract: Initiation of breast-feeding within 1 h after birth has been associated with reduced neonatal mortality in a rural Ghanaian population. In South Asia, however, breast-feeding patterns and low birth weight rates differ and this relationship has not been quantified. Data were collected during a community-based randomized trial of the impact of topical chlorhexidine antisepsis interventions on neonatal mortality and morbidity in southern Nepal. In-home visits were conducted on d 1-4, 6, 8, 10, 12, 14, 21, and 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
273
1
29

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 294 publications
(315 citation statements)
references
References 17 publications
12
273
1
29
Order By: Relevance
“…8 The previous studies analyzing breast-feeding practices found that infants partially or predominantly breast-fed had an increased risk of neonatal mortality compared with infants exclusively breast-fed. 14,15 Further analyses of the breast-feeding practices in Southern India, including duration and exclusivity could provide more accurate information on the proportion of neonatal deaths that could be prevented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The previous studies analyzing breast-feeding practices found that infants partially or predominantly breast-fed had an increased risk of neonatal mortality compared with infants exclusively breast-fed. 14,15 Further analyses of the breast-feeding practices in Southern India, including duration and exclusivity could provide more accurate information on the proportion of neonatal deaths that could be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…As with previous studies, 14,15 infants who died within the first 48 h of birth were excluded to minimize the potential for reverse causation bias. Additionally, to reduce likelihood of recall bias for time of breast-feeding initiation, only infants for whom the first visit occurred within 7 days after birth were included in the analysis.…”
Section: Vasin Parent Trial and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, delay in initiating breastfeeding beyond 24 hours of birth is associated with 85 % risk of dying. 3 It also reported in the same study that only 50% of the world infants initiate breastfeeding within an hour thus leaving a 50 % practice gap.…”
Section: Introductionmentioning
confidence: 91%
“…1 Several studies have proven the protective effect of colostrum against varied pathogenic microorganisms that have detrimental effects to the survival of the newborn baby especially during the immediate postpartum period. 2,3 Delayed breastfeeding is consequently associated with high neonatal morbidity and mortality especially during the first week of life. 2 In one multicentre study conducted in Ghana, India, Nepal and Tanzania, EBFI was found curb risk of neonatal deaths by 33 % if commenced within an hour of birth.…”
Section: Introductionmentioning
confidence: 99%